Isolation and characterization of novel peptides from fermented products of Lactobacillus for ulcerative colitis prevention and treatment - Dong He; Wen Zeng; Yi Wang; Yifan Xing; Kang Xiong; Nan Su; Chong Zhang; Yuan Lu; Xinhui Xing (Food Science and Human Wellness)
Ulcerative colitis (UC) is an incurable and highly complex digestive disease affecting millions of people worldwide. Compared to the current therapeutic drugs, bioactive peptides are more promising and safe substances as functional foods or drugs for the prevention and treatment of UC. The alcohol-soluble components from fermentation broth by fresh wheat germ and apple (AC-WGAF) were found to be effective in UC prevention in dextran sulfate sodium-induced mice in vivo. Herein, 4 novel peptides are identified from AC-WGAF by membrane ultrafiltration, recycling preparative high-performance liquid chromatography, and matrix-assisted laser desorption–ionization time-of-flight/time-of-flight mass spectrometry, possessing anti-colitis activity via using an in vitro model. One of those peptides named T24 (PVLGPVRGPFPLL) exhibited the most remarkable anti-colitis activity by preventing tight junction protein loss, maintaining epithelial barrier integrity, and promoting cell proliferation during in vitro and in vivo studies by regulating mitogen-activated protein kinase signaling pathways. Thus, T24 is a promising peptide as a functional food or novel drug for UC prevention and treatment.